Implementasi Integrasi Jaringan Ipv4 Dan Jaringan Ipv6 Pada Local Area Network (Lan) Dengan Sistem Tunneling - Basuki, Mardianto; Jusak, Jusak; Sukmaaji, Anjik (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
The development of computer network technology is currently growing exponentially along with the increasing users who make use of the computer network. In a computer network is addressing systems named IP address.Public IP address in use today is IPv4; The user who added the more led to exhaustion of IPv4 addresses are available on the internet. To overcome these problems developed types of IPv6. IPv4 can not directly linked with the IPv6 tunneling system is required to integrate both the IPS in a network of computers.In this final project will design a system of tunneling in a network of computers that use IPv6 as a server and client in which IPv6 data packet takes through the network IPv4 which is still existing and there occurs the process of Christianization engkapsulasian IP address, either peng-enkapsulasian IPv6 in IPv4 packet or vice versa.When using file-sharing whereby and the webserver by doing a test upload and download by the client. Expected by the existence of this research both different IP address generation can be integrated in a network of computers. Keywords: IP address, IPv4, IPv6, client, dan server,tunneling